Translational enhancing activity in 5′ UTR of peste des petits ruminants virus fusion gene - Chulakasian, Songkhla; Chang, Tien‐Jye; Tsai, Ching‐Hsiu; Wong, Min‐Liang; Hsu, Wei‐Li (The FEBS journal, 2013)
The fusion gene of peste des petits ruminants virus (PPRV‐F), a paramyxovirus, contains an unusual long 5′ untranslated region (5′ UTR) with a high GC content that is capable of folding into secondary structure proximally to the 5′ cap. Sequence analysis further suggested that the proximal end of this UTR contains a nine‐nucleotide sequence which could perfectly complement the 18S rRNA and might affect translation through mRNA–rRNA interaction. Based on these features, we examined the functional role of the proximal PPRV‐F 5′ UTR on translational efficiency compared with two other morbilliviruses. From reporter gene assays, PPRV‐F 5′ UTR functioned as a strong enhancer of translational efficiency independent of cell and gene specificity. Northern blot analysis of the accumulative RNA levels and mRNA stability suggested that elevated gene expression driven by PPRV‐F 5′ UTR was accompanied by an increased mRNA level and enhanced mRNA stability. Deletion analysis identified the complementary sequence and distal nucleotides necessary for the enhancing activity, and results suggest RNA structural conformation is important. Taken together, we conclude that the proximal PPRV‐F 5′ UTR functions as a translational enhancer by promoting translation efficiency and mRNA stability. We report a translational enhancer in PPRV‐F 5′ UTR, independent of cell‐ and gene‐specificity. Northern blotting analysis suggested elevated gene expression was accompanied by an increased mRNA level and enhanced mRNA stability. Moreover, deletion analysis identified the complementary sequence to 18S rRNA and distal nucleotides are necessary for the enhancing activity driven by PPRV‐ F 5′ UTR